Peran Kepala Sekolah Dalam Peningkatan Kompetensi Profesionalisme Guru Sekolah Dasar Negeri Di Kabupaten Lombok Tengah - Misroyani, Misroyani; Witono, A. Hari (Primera Educatia Mandalika: Elementary Education Journal, 2024)
This study aims to obtain an objective and comprehensive picture of the role of the principal in improving the professional competence of teachers at Public Elementary Schools in Central Lombok Regency. This study uses a descriptive qualitative research approach with data collection techniques through observation, interviews, and documentation. The subjects in the study were principals, teachers, education personnel and supervisors. Data were analyzed by reducing, displaying, drawing conclusions and verifying data. Based on the results of the analysis of the data obtained, it shows that the principal has an important role in improving the professional competence of teachers in their respective work environments, the mastery of professional competence of teachers at Public Elementary Schools in Central Lombok Regency is included in the moderate qualification, and there is a positive and significant relationship between the role of the principal and the mastery of competence of teachers at Public Elementary Schools in Central Lombok Regency.